The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/bit.22267
|View full text |Cite
|
Sign up to set email alerts
|

Syntrophic interactions among anode respiring bacteria (ARB) and Non‐ARB in a biofilm anode: electron balances

Abstract: We demonstrate that the coulombic efficiency (CE) of a microbial electrolytic cell (MEC) fueled with a fermentable substrate, ethanol, depended on the interactions among anode respiring bacteria (ARB) and other groups of micro-organisms, particularly fermenters and methanogens. When we allowed methanogenesis, we obtained a CE of 60%, and 26% of the electrons were lost as methane. The only methanogenic genus detected by quantitative real-time PCR was the hydrogenotrophic genus, Methanobacteriales, which presuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
149
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 222 publications
(166 citation statements)
references
References 51 publications
7
149
0
3
Order By: Relevance
“…Another study showed that a flowthrough system fed with acetate (5.4 kg chemical oxygen demand [COD]/m 3 /day) had increasing methane production as the anode potential decreased in the anode potential range of Ϫ300 mV Ͻ E an Ͻ Ϫ100 mV versus SHE (55). In an ethanol-fed MFC, hydrogenotrophic Methanomicrobiales was the only detected methanogen (38). In MEC systems, hydrogenotrophic methanogenesis has been proposed as the main methanogenic pathway due to hydrogen flux to the anode (7,26).…”
mentioning
confidence: 99%
“…Another study showed that a flowthrough system fed with acetate (5.4 kg chemical oxygen demand [COD]/m 3 /day) had increasing methane production as the anode potential decreased in the anode potential range of Ϫ300 mV Ͻ E an Ͻ Ϫ100 mV versus SHE (55). In an ethanol-fed MFC, hydrogenotrophic Methanomicrobiales was the only detected methanogen (38). In MEC systems, hydrogenotrophic methanogenesis has been proposed as the main methanogenic pathway due to hydrogen flux to the anode (7,26).…”
mentioning
confidence: 99%
“…Previous studies suggest the existence of competition between methanogens and electricity producing bacteria for H 2 (Freguia et al, 2008) and acetate (Virdis et al, 2009). Methane production has been observed in MFCs fed with fermentable substrates (glucose and ethanol) (Freguia et al, 2007;Kim et al, 2007;Lee et al, 2008;Parameswaran et al, 2009), and in acetate fed MFCs at the early stages of enrichment when using digester sludge inoculum (Kim et al, 2005). However the serial transfer of enriched electrodes under exo-electrogenic conditions diminishes methane production in acetate fed MFCs, suggesting that acetate-oxidizing exoelectrogens are capable of out-competing acetoclastic methanogens as it would be thermodynamically favourable (Lovley & Phillips, 1988).…”
Section: Analyses Of Archaeal Community Composition Dynamicsmentioning
confidence: 99%
“…Using short-term kinetic tests with H 2 , Freguia et al (2008) showed that part of the anodic H 2 produced by glucose fermentation was used by hydrogen-oxidizing methanogens. By electron balance and finding that the hydrogenotrophic methanogenic genus Methanobacteriales was the only methanogen present in the anodic biofilm (~4% of the total microbial community), Parameswaran et al (2009) demonstrated that the electrons available in H 2 from ethanol fermentation were routed to CH 4 . A hydrogenotrophic methanogen, Methanobacterium bryantii, dominated the archaeal community in a cellulose-fed MFC (Ishii et al, 2008), whereas acetoclastic methanogens accounted for ~19% and hydrogenotrophic methanogens accounted only for ~5% of the total microbial community in a glucose-fed MFC (Chung & Okabe, 2009).…”
Section: Analyses Of Archaeal Community Composition Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these inhibitors suppress methanogenesis only temporarily, which can resume once the chemicals are removed from solution. They are not considered a viable strategy for long-term and large-scale MES systems because the amount added (up to 50 mM BES) can be toxic to other microorganisms, and the use of these chemicals at high concentrations can be uneconomical (9). Like BES and methyl fluoride, alamethicin is an inhibitor of methanogenesis, as demonstrated by a previous study on different peptide antibiotics (10).…”
mentioning
confidence: 99%